The impact of blended learning in improving the reaction, achievement and return on investment of industrial automation training - Mackay, Stephen George (Curtin University, 2008)
There has been a significant increase in the level of remote or distance learning using the Internet, often referred to as e-learning or online education. E-learning is often combined with classroom instruction and on-the-job training and this is referred to as blended learning. The purpose of this research is to investigate the impact blended learning has in improving engineering training in the engineering field of industrial automation. This is especially in improving the reaction, achievement and return on investment of learners compared to that of only the traditional classroom or e-learning approaches. One of the gaps in current research is the examination of the impact of blended learning in improving engineering training. The research revealed significant growth in the use of e-learning for engineers and technicians. There would however appear to be a large number of engineers and technicians who were disappointed with their experiences of e-learning. Significant concerns were also identified in the efficacy of e-learning and the lack of hands-on experience in this form of training for engineers and technicians. Suggestions are made as a result of the research into addressing these issues.